The Impact of Nimodipine Administration through Feeding Tube on Outcomes in Patients with Aneurysmal Subarachnoid Hemorrhage - Fadumo Ahmed Isse; Yasmeen El Hajj Abdallah; Sherif Hanafy Mahmoud (Frontiers Media S.A., 2020)
PURPOSE: Delayed cerebral ischemia (DCI) and vasospasm are the main challenges contributing to unfavorable outcomes following aneurysmal subarachnoid hemorrhage. Nimodipine has been shown to decrease the incidence of delayed cerebral ischemia and improve outcomes. In patients who are unable to swallow, nimodipine tablets are crushed and administered through enteral feeding tubes. However, it is not clear whether this may result in reduced clinical effectiveness. The aims of the study were to investigate the impact of nimodipine administration through enteral feeding tubes, in the first 7 days and over the 21-days period on patient outcomes. METHODS: A retrospective chart review of subarachnoid hemorrhage patients admitted at the University of Alberta Hospital, Edmonton, Alberta, Canada was carried out. Logistic regression modelling was utilized to identify predictors of vasospasm and delayed cerebral ischemia. Main outcome measures were angiographic evidence of moderate to severe vasospasm, development of delayed cerebral ischemia and hospital mortality. RESULTS: 85 patients were included. Following adjustment for disease severity, nimodipine administration technique was associated with vasospasm in the first 7 days of patient admission where patients receiving nimodipine via enteral feeding tubes had increased odds of vasospasm compared to those administered it as whole tablets (OR 8.9, 95% CI 1.1-73.1, p value 0.042). When analyzed over the 21-day period, nimodipine administration by feeding tube was associated with increased odds of DCI compared to whole tablets (OR 38.1, 95% CI 1.4-1067.9, p value 0.032). CONCLUSIONS: Our findings suggest that nimodipine administration via enteral feeding tubes may be associated with vasospasm and DCI in subarachnoid hemorrhage patients secondary to reduced exposure. Prospective studies are needed to confirm such association and alternate methods of administration should be explored to ensure patients are getting the benefits of nimodipine.